Pelatihan Terapi Relaksasi Hypnobirthing Untuk Tenaga Kesehatan Dalam Rangka Meningkatkan Pelayanan Kesehatan Ibu Dan Anak - Lutfiana Puspita Sari; Triwik Sri Mulati (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: labor pain is a real problem for maternity mothers, as many as 90% of women experience pain during childbirth. Mothers who are about to give birth expect to be able to give birth with a sense of comfort, but in reality many health workers, especially midwives, do not understand how to accompany mothers in labor and teach the correct relaxation techniques to reduce labor pain. The hypnobirthing relaxation technique is a natural pain reduction program by utilizing the subconscious mind to believe that childbirth is a natural, comfortable, and normal process that pregnant women can learn during their pregnancy. Methods: Method this study is used relaxation hypnobirthing intervention. The sample of this study were all midwives in the South Klaten Public Health Center area. The researcher demonstrated hypnobirthing relaxation and then the respondents practiced it in pairs. Results: the average value of the knowledge of the midwives before the training on hypnobirthing relaxation was only 50, after the training the knowledge increased by 90. Hypnobirthing relaxation training can increase knowledge and skills of midwives to in assisting pregnant women during their pregnancy and lead pregnant women to a comfortable, smooth, natural, and normal labor. Conclusion: Hypnobirthing relaxation training for midwives can increase their knowledge in assisting mothers in childbirth so that they can relax in the face of childbirth.